(untitled) (Indian Journal of Child Health, 2020)
Background: Foreign body aspiration (FBA) is a common medical emergency in childhood. It may have serious and lethal outcomes if not managed promptly. The clinician must suspect FBA on the grounds of history, even if clinical and radiological findings are not supportive. Objective: The objective of this study was to study the clinicoepidemiological profile of FBA in children. Materials and Methods: This hospital-based retrospective study was carried out in the Department of Pediatric Surgery between October 2017 and November 2019. A total of 15 cases of FBA reported in children were analyzed. All these cases presented in amedical emergency. History taking and clinical examination were followed by radiological evaluation and bronchoscopy in all the cases. Results: We reported 15 cases of FBA in children in our setting for 2 years. There were 11 boys (73%) and four girls (27%). Most of the cases reported within 3 days of aspiration, but the time of presentation was as long as 6 months. Rigid bronchoscopy was performed in all cases, and Magill forceps were used in two cases. Spontaneous expulsion of the FB occurred in two cases. All cases were subjected to check bronchoscopy. Conclusion: The age group <3 years have the highest risk for FBA. ronchoscopy is a skilled procedure and requires the utmost care to avoid lethal complications. The clinician must not get hesitant in doing repeat bronchoscopy in multiple settings to ensure successful retrieval of the FB.